Guided evolutionary game algorithm of unstructured P2P network - Guohui ZHU; Chunlan LU; Rui ZHANG (Dianxin kexue)
In order to promote the cooperation among the nodes which exist in dynamic and open peer-to-peer network,G-SLACER algorithm was provided by introducing pacesetter nodes.30% of network nodes were initialized to pacesetter nodes.In the process of topology reconstruction,a guided link to the most advantage node was added.To encourage studies between nodes,the payoff of the whole network was increased.The experimental results show that the G-SLACER algorithm has good generality for different sizes of networks,and it enhances the stability of CCP.Compared with other evolutionary game algorithms,cooperation state of P2P network formed by G-SLACER algorithm appears earlier and more stable.